2018
DOI: 10.1096/fj.201701143rr
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule associated tumor suppressor 1 interacts with mitofusins to regulate mitochondrial morphology in endothelial cells

Abstract: Mitochondria are dynamic organelles that are able to change their morphology and cellular distribution by either fission or fusion. However, the molecular mechanisms controlling mitochondrial dynamics in vascular endothelial cells (ECs) remain largely unknown. In this study, we observed that knockdown of microtubule-associated tumor suppressor 1 (MTUS1) in ECs inhibited tube formation and migration, accompanied with decreased promigratory signalings. We showed that MTUS1 was localized in the outer membrane of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…We observed only the ATIP1 isoform in HUVECs ( Supplemental Fig. 1 (C) ), which is in accord with previous reports [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed only the ATIP1 isoform in HUVECs ( Supplemental Fig. 1 (C) ), which is in accord with previous reports [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Seibold et al used forced expression analysis of ATIP1 [ 29 ] and Wang et al used polyclonal antibody against ATIP [ 30 ] to demonstrate that ATIP1 localizes mainly to mitochondria. Wang et al reported that ATIP1 appeared in two bands in their expression system, which is consistent with our result ( Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, MTUS1 , possibly contributing to protection against pro-inflammatory response of endothelial cells 54 , may be involved in the anti-inflammatory defense at 2 weeks. In addition, MTUS1 has recently been shown to be involved in mitochondrial motility, fusion and in the maintenance of mitochondrial morphology 55 and its reduction at 2 weeks may serve to support the evidence for alterations of mitochondrial content and function early after surgery. At 52 weeks, downregulated genes comprise interferon-γ mediated signaling, in line with the time course of inflammatory markers of the present study and the lower expression of inflammation-related genes in a previous study 56 .…”
Section: Discussionmentioning
confidence: 85%
“…Apart from neurons, studies in other mammalian cells have linked microtubules to fission, specifically through microtubule-associated proteins (MAPs). For example, in mammalian endothelial cells, microtubule-associated tumor suppressor 1 (Mtus1) binds to mitofusins, fusion-regulating proteins on the outer mitochondrial membrane, and helps mediate fusion [ 56 ]. Knocking out Mtus1 results in decreased fusion and shorter mitochondria [ 56 ].…”
Section: Microtubules and Mitochondrial Dynamics In Neurons And Mamma...mentioning
confidence: 99%